Farmer's knowledge on insect pest and control in paddy field at Department of Agriculture, Merlimau, Malacca / Siti Hafsah Mohd Rahim - Mohd Rahim, Siti Hafsah (Faculty of Plantation and Agrotechnology, 2016)
Each farmers have their own perception on insect pest and how to control insect pest in paddy field. The differences on the practices will carry different result in yield. Evaluating farmer's knowledge on insect pest and control useful to set research agenda, and to know the understanding of farmers about types of insect pest and how to control the insect pest in paddy field. The objectives of this study are to determine farmer's knowledge on insect pest and control in paddy field and to identify types of insect pest in paddy field. A semi structured survey on paddy, farmer's background, knowledge and control action were conducted on 30 March 2016. The background of the study was referred to the age, gender, experience handling paddy field, wages, area/acres, education level and activities practices in paddy field. Most of the farmers were range between (30-70) years old, and most of them were around age 50 and above. For education level the high percentage were (43.1%) of farmers that finished their study in secondary school with total of farmers were 25 of respondent and the low percentage were (3.4%) of farmers that finished their study in diploma/degree with total of farmers only 2 respondent. Most of the farmers (41.4%) have experience 10 years and above in managing paddy field. Even though their age were 50 and above, but their knowledge were still lack in to identification on different types of insect pest. Meanwhile, the highest severity of insect pest were golden apple snail and paddy bug. Farmers were still lacking on the knowledge of the insect pest and how to control based on the time table given by Department of Agriculture Merlimau. Training and short module need to be done to educate farmer 's knowledge on insect pest and control need to take into consideration for better management and decision making.